Factors influencing readiness to implement digital audit among internal auditors of the Malaysian public sector - Ismail, Suhaiza; Mokhtar, Norsyahida; Ahmad @ Abdul Mutalib, Hawa (Emerald Publishing, 2024)
Purpose – This paper aims to examine the factors that influence the readiness of public sector internal auditors of the Accountant General’s Department (AGD) in Malaysia to implement digital audit. Design/methodology/approach – This study used an online questionnaire survey that was administered to a population of 124 internal auditors of the AGD, Malaysia. The readiness was measured in two ways: change commitment (CCOM) and change efficacy (CEFF), whereas the predictors of readiness encompass three factors: change valence, task knowledge and task availability. A partial least squares modelling using the SmartPLS 4 version was used to test the hypotheses. Findings – The results reveal that change valence, task knowledge and task availability are positively significant factors influencing the CCOM of the AGD to implement digital audit. However, change valence is the only factor influencing CEFF. Originality/value – This study offers useful empirical evidence on determinants of readiness to implement digital audit among internal auditors in the public sector, which is crucial towards supporting the Malaysian Government’s digital transformation agenda.